NanoElectronics roadmap for Europe: From nanodevices and innovative materials to system integration. (May 2019) - Ahopelto, J.; Ardila, G.; Baldi, L.; Balestra, F.; Belot, D.; Fagas, G.; De Gendt, S.; Demarchi, D.; Fernandez-Bolaños, M.; Holden, D.; Ionescu, A.M.; Meneghesso, G.; et al.
Highlights: This paper introduces the new NanoElectronics Roadmap for Europe covering topics from Nanodevices beyond CMOS and Innovative Materials to system Integration. It has been worked by the European CSA project NEREID which has been funded by the European Union's Horizon 2020 research and innovation programme under grant agreement No 685559. The NEREID roadmap gives a projection of the evolution of many Figures of Merit (FoMs) vs time for covering the most promising technologies including novel functionalities. The NEREID roadmap delivers an understanding of the dependencies between short/ medium term (e.g. More Moore and More than Moore) and long/very long term (e.g. Beyond CMOS) activities. The NEREID roadmap is based on a strong interaction between application and technology experts, coming from leading research players in industry and academia, especially by face to face exchange during many Workshops. The NEREID roadmap is created in a combination of a top-down approach, which is application driven, and a bottom-up one, based on planned technology evolution to prompt new ideas for disruptive products and applications. Abstract: The NEREID project ("NanoElectronics Roadmap for Europe: Identification and Dissemination") is dedicated to mapping the future of European Nanoelectronics. NEREID's objective is to develop a medium and long term roadmap for the European nanoelectronics industry, starting from the needs of applications to address societal challenges and leveraging the strengths of the European eco-system. The roadmap will also identify promising novel nanoelectronic technologies, based on the advanced concepts developed by Research Centres and Universities, as well as identification of potential bottlenecks along the innovation (value) chain. Industry applications include Energy, Automotive, Medical/Life Science, Security, loT, Mobile Convergence and Digital Manufacturing. The NEREID roadmap covers Advanced Logic and Connectivity, Functional Diversification (Smart Sensors, Smart Energy and Energy for Autonomous Systems), Beyond-CMOS, Heterogeneous Integration and System Design as well as Equipment, Materials and Manufacturing Science. This article gives an overview of the roadmap's structure and content.